2019
DOI: 10.1186/s41118-019-0069-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variations in unmet need for family planning in Ghana: 2003–2014

Abstract: Ghana has long prioritized family planning as a key strategy for improving health and socioeconomic development. However, despite the heavy investments in the sector over the last decade, the family planning program has not successfully improved the country's family planning indicators. In this study, we describe the spatial and temporal patterns of unmet need for family planning from 2003 to 2014 and mainly estimate the socioeconomic factors affecting it. Using data from the 2003, 2008, and 2014 Ghana Demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 10 publications
4
14
0
Order By: Relevance
“…In essence, this is possibly down to the considerably poorer socio-economic profiles of these regions compared to the southern regions. These regions have the lowest female education and the highest female poverty rate in the country which may underpin their low prevalence of modern contraceptives [18]. A similar situation has been observed in Nigeria where there is a considerable disparity between the north and south in relation to contraceptive use and was found to be explained mainly by socio-economic inequalities as well as ideational factors [19].…”
Section: Discussionmentioning
confidence: 58%
“…In essence, this is possibly down to the considerably poorer socio-economic profiles of these regions compared to the southern regions. These regions have the lowest female education and the highest female poverty rate in the country which may underpin their low prevalence of modern contraceptives [18]. A similar situation has been observed in Nigeria where there is a considerable disparity between the north and south in relation to contraceptive use and was found to be explained mainly by socio-economic inequalities as well as ideational factors [19].…”
Section: Discussionmentioning
confidence: 58%
“…Women from poor households show a greater risk of nonmarital childbirth and this supports the findings of many related studies in sub-Saharan Africa [ 3 , 18 , 19 , 25 , 26 ]. Women from rich households have a significantly lower risk of unmet need for family planning compared to women from poor households [ 27 ], clearly because they may afford and access sexual and reproductive health services such as family planning and abortion services, information, and education to prevent childbirths outside marriage. On the contrary, there appears to be some evidence associating women from rich households with a significantly higher likelihood of nonmarital childbearing [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clear trend toward lower incidence of overachieved fertility could be related to decreasing unmet need for family planning in sub-Saharan Africa. A Study by Nyarko et al [ 7 ] using the 2003, 2008 and 2014 Ghana Demographic and Health Survey data has shown that there is a declining proportion of women not using contraception when they don’t want to get pregnant.…”
Section: Discussionmentioning
confidence: 99%